Novel high-entropy alloy binding phase diamond composite material and preparation method thereof
By adopting the new CoxNiyTizZr1-x-y-z high-entropy alloy as the bonding phase and hot-pressed sintering with bare diamond powder, the problem of insufficient interface bonding in traditional diamond composite materials is solved, and the wear resistance and bending strength of the material are significantly improved.
Patent Information
- Application Number
- CN202510038843.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-10
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2045-01-10
AI Technical Summary
The low content of diamond in traditional diamond composite materials leads to insufficient performance of the bonded phase, the retention ability of the diamond, and the interface bonding strength between the bonded phase matrix and diamond, which affects the material's wear resistance and hardness.
The new CoxNiyTizZr1-x-y-z high-entropy alloy is used as the bonding phase. High-entropy alloy powder is prepared by ultrasonic atomization method, and mixed with bare diamond powder through a three-dimensional mixer. The composite material is prepared by a rapid hot press sintering process, and the sintering temperature and time are adjusted to optimize the interface combination.
The bending strength and wear resistance of diamond composite materials are improved, the wear amount of the material is reduced, the friction coefficient is reduced, and the wear ratio is improved, showing excellent wear resistance and flexural strength.
Smart Images

Figure CN119776713A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a metal-based diamond composite material, in particular to a novel high-entropy alloy bonding phase diamond composite material and a preparation method thereof, and belongs to the field of composite material preparation. Background Art
[0002] Traditional synthetic diamond composites are widely used in the fields of heat conduction, abrasive tools, diamond grinding wheels and processing. The diamond content of traditional diamond composites is low, about 10% to 20%. Due to the low content of diamond, the performance of the bonding phase, the diamond retention ability and the interface bonding strength between the bonding phase matrix and the diamond are the key factors affecting the performance of diamond composites. The commonly used method for preparing diamond composites is sintering, and the sintering temperature is usually above 1000°C. However, the thermal stability of diamond is relatively poor, and diamond graphitization is prone to occur. If the diamond in the composite material is graphitized, it will affect the bonding between the diamond and the bonding phase matrix, and will also reduce the hardness and wear resistance of the diamond itself, resulting in failure of the composite material. At the same time, the wettability between the diamond and the metal bonding phase is relatively poor, and it is difficult to form a strong interface bond, which makes it easy for diamond tools to cause abrasive spalling during use. In order to solve the above problems, coated diamond is usually used. For example, in the article "Effect of diffusion barrier and interfacial strengthening on the interface behavior between high entropy alloy and diamond" published in 2021, they introduced Ti-coated diamond and Fe 25 Co 25 Cr 25 Ni 25It was found that a TiC layer was generated in situ at the interface between diamond and the substrate, which played the role of diffusion barrier and strengthening layer, improved interface bonding, and inhibited diamond graphitization. The flexural strength and friction coefficient of the material were 925.5MPa and 0.15, respectively, and the mechanical properties and wear resistance of the material were relatively good. In the article "Effect of Ti / NiCoating of Diamond Particles on Microstructure and Properties of High-EntropyAlloy / Diamond Composites" published in 2019, they introduced Ti / Ni coated diamonds, and the flexural strength and friction coefficient of the prepared diamond composites were about 750MPa and 0.05, respectively. In the article "Enhancedproperties of a novel medium-entropy alloy base diamond composite by introducing coherent L12phase at interface" published in 2024, they used a medium-entropy alloy MEA:Co 34.07 Ni 33.94 Cr 13.57 Ti 7.82 Al 5.17 M 5.43 at% (M=Mo / W / Ta / Zr / Hf) and bare diamond powder were synthesized by hot pressing and sintering to form a diamond composite material. An intermediate layer composed of L12 phase and chromium carbide was formed in situ between the diamond and the metal matrix. The intermediate layer improved the bonding state between the diamond and the metal matrix and alleviated the graphitization of the diamond under service. The average friction coefficient of the diamond composite material was 0.1310 and the friction loss was small. The wear ratio experiment was also carried out, and it was found that the wear ratio of the diamond composite material with medium entropy alloy matrix was 706, and the material had good wear resistance. From this study, it can be seen that the development of a new bonding phase alloy system, improving the interface bonding between diamond and matrix, and then improving the wear resistance of composite materials is a direction with great development potential. Summary of the invention
[0003] The present invention is directed to developing a high entropy alloy binder phase diamond composite material with excellent wear resistance after sintering at about 1000-1100°C. Co x Ni y Ti z Zr 1-x-y-zHigh entropy alloy powder. By adjusting the composite material components, sintering temperature and sintering time, the designed composite material has excellent wear resistance.
[0004] The technical solution of the present invention is: The present invention discloses a novel high entropy alloy bonding phase diamond composite material with excellent wear resistance, which consists of bonding phase alloy and diamond, wherein the metal bonding phase content is 80-90 vol.%, and the diamond content is 20-10 vol.%; The element components and atomic percentages of the bonding phase alloy are: Co is 20-30%, Ni is 20-30%, Ti is 20-30%, and Zr is the balance; The diamond has a particle size of 170-200 meshes.
[0005] Preferably, the diamond comprises bare diamond particles having a complete crystal form.
[0006] As a further preference, the model of the diamond is DSD80.
[0007] Preferably, a novel high entropy alloy bonding phase diamond composite material is provided, wherein in the bonding phase, by molar percentage, Co:Ni:Ti:Zr=1:1:1:1.
[0008] As a preferred embodiment, the novel high entropy alloy binder phase diamond composite material with excellent wear resistance has a metal binder phase content of 85-90% and a diamond content of 15-10 vol.%. As a further preferred embodiment, the metal binder phase content is 87.5% and the diamond content is 12.5 vol.%.
[0009] The preparation method of the novel high entropy alloy binder phase diamond composite material of the present invention comprises: weighing required high entropy alloy binder phase powder and bare diamond powder according to the configuration ratio, mixing them, performing pre-compression deformation and then hot pressing and sintering to obtain the composite material; the hot pressing and sintering temperature is 1010-1100°C.
[0010] As a preferred solution, the high entropy alloy binder phase and the bare diamond powder are mixed using a three-dimensional mixer.
[0011] As a preferred solution, the hot pressing sintering temperature is 1040-1060°C, the sintering time is about 10-20 minutes, and the sintering pressure is about 30-50 MPa.
[0012] The preparation method of the novel high entropy alloy binder phase diamond composite material with excellent wear resistance comprises the following steps: Ingredients: Calculate the required contents of metals Co, Ni, Ti, and Zr with a purity of 99.9% according to atomic percentage; and weigh the required diamond powder.
[0013] Powder preparation: The high entropy alloy binder phase powder is prepared by ultrasonic atomization. This method can obtain a large number of powders with high sphericity, and the prepared powder has good fluidity and formability, which is conducive to improving the uniformity of composite material performance.
[0014] Powder mixing: The high entropy alloy binder phase powder and diamond powder weighed according to the configuration ratio are mixed by a three-dimensional mixer for 24 hours to achieve uniform mixing of the binder phase and bare diamond powder. This method avoids the safety accidents and impurities that may be caused by the mechanical ball milling method.
[0015] Sintering: The specific sintering process is to first evacuate to 5~50Pa, heat up from room temperature to 715~800℃ at a heating rate of 80~120℃ / min, keep warm for 1~3min, and pressurize to a forming pressure of 30~50MPa; then heat up to a sintering temperature of 1010~1100℃ at a heating rate of 80~130℃ / min, and keep warm for 8~24min.
[0016] The diamond powder includes bare diamond powder.
[0017] The flexural strength of the high entropy alloy bonding phase diamond composite material designed and prepared by the present invention is not less than 512.26MPa. After the friction and wear test, the wear amount of the material does not exceed 0.0076g, and the friction coefficient of the material does not exceed 0.5 during the friction of 600s to 1800s.
[0018] By regulating the sintering temperature and sintering time, the flexural strength of the high-entropy alloy bond phase diamond composite material is not less than 642.58MPa. After the friction and wear test, the wear amount of the material is 0.0013g. During the friction period of 600s~1800s, the friction coefficient of the material is about 0.05, and the wear ratio of the material is 843.
[0019] Compared with the prior art, the present invention has the following advantages: 1. The present invention adopts a new type of Co x Ni y Ti z Zr 1-x-y-z High entropy alloys, as metal binder phases of diamond composites, have introduced a new binder phase system into the field of diamond composites, in which the binder phase elements Co and Ni have good lattice matching with diamond, and Ti and Zr are carbide-forming elements.
[0020] 2. The present invention uses a three-dimensional powder mixer to mix powder and adopts a rapid hot pressing sintering process to prepare a high entropy alloy binder phase diamond composite material. The method is carried out under normal pressure throughout the process, has a simple process flow, a short production cycle, low production cost, and is suitable for large-scale production.
[0021] 3. Co of the present invention x Ni y Ti z Zr 1-x-y-z -Diamond composites have excellent wear resistance and maintain comparable bending strength to other alloy composites.
[0022] 4. The present invention provides sintering parameters of a new type of high entropy alloy binder phase diamond composite material with excellent wear resistance. By adjusting the sintering temperature and sintering time during sintering, a diamond composite material with better wear resistance can be prepared. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 For comparative example 1 Co x Ni y Ti z Zr 1-x-y-z The high entropy alloy binder phase and bare diamond particles were sintered at 1000℃; and the surface microstructure of the composite material was observed after being kept at 1000℃ for 10 min.
[0024] Figure 2 For comparative example 2 Co x Ni y Ti z Zr 1-x-y-z The high entropy alloy binder phase and bare diamond particles were sintered at 1000℃; and the surface microstructure of the composite material was observed after being kept at 1000℃ for 20 min.
[0025] Figure 3 Example 1 Co x Ni y Ti z Zr 1-x-y-z The high entropy alloy binder phase and bare diamond particles were sintered at 1050℃; and the surface microstructure morphology of the composite material was observed after being kept at 1050℃ for 10 min.
[0026] Figure 4 This is the surface microstructure morphology of the diamond composite material of Comparative Example 1 after friction and wear testing.
[0027] Figure 5 This is the surface microstructure morphology of the diamond composite material of Comparative Example 2 after friction and wear testing.
[0028] Figure 6This is the surface microstructure morphology of the diamond composite material in Example 1 after friction and wear testing.
[0029] Figure 7 This is the energy spectrum image at the interface of the diamond composite material of Comparative Example 1.
[0030] Figure 8 This is the energy spectrum image at the interface of the diamond composite material of Comparative Example 2.
[0031] Fig. 9 This is the energy spectrum image at the interface of the diamond composite material in Example 1.
[0032] Fig.10 The test force-friction force-friction coefficient curves of the diamond composite materials of Comparative Examples 1, 2 and Example 1 after friction and wear testing.
[0033] Fig.11 It is the transverse fracture strength of the diamond composite materials of Comparative Examples 1, 2 and Example 1.
[0034] from Figure 1 , 2 It can be seen from Figures 1 and 3 that there is obvious diamond particle shedding in Comparative Examples 1 and 2, while the crystal form of diamond in Example 1 is more complete, the surface is smoother, and the traces of ablation are not obvious, which indicates that the sintering temperature is increased, and the combination between diamond and the binder phase is tighter.
[0035] from Figure 4 , 5 It can be seen from Figures 6 and 7 that after the friction and wear test, the surfaces of the samples of Comparative Examples 1 and 2 have more obvious traces of friction by the Si3N4 ball, and the surface of the sample of Example 1 is smoother.
[0036] from Figure 7 , 8 As can be seen from Figures 9 and 10, in the samples of Comparative Example 2 and Example 1, there is enrichment of Zr element at the interface between diamond and the bonding phase matrix, indicating that there may be an interfacial reaction between the bonding phase and diamond, and the interfacial bonding strength is higher.
[0037] from Fig.10 It can be seen that within 600-1800s of Si3N4 ball friction, the friction coefficients of the three samples tend to be stable, the friction coefficients of comparative examples 1 and 2 are similar, about 0.4, while the friction coefficient of embodiment 1 is relatively low, about 0.05, and the wear resistance of embodiment 1 is better, indicating that the wear resistance of the material can be improved by adjusting the sintering temperature and sintering time.
[0038] from Fig.11It can be seen that with the increase of sintering time and sintering temperature, the transverse rupture strength of the sample gradually increases, indicating that the bonding between diamond and the bonding phase may be better, and the sample in the present invention has a transverse rupture strength comparable to that of other materials, and has good comprehensive performance. DETAILED DESCRIPTION
[0039] The present invention is described in detail below with reference to specific examples.
[0040] In Example 1, the wear ratio is tested according to JB / T 3235-2023.
[0041] Comparative Example 1 1. Material preparation: Prepare Co x Ni y Ti z Zr 1-x-y-z High entropy alloy powder: Co, Ni, Ti and Zr single-element raw materials with a purity of 99.9% are made by ultrasonic atomization to form a high-entropy alloy powder with a composition of Co x Ni y Ti z Zr 1-x-y-z (at%, x=25, y=25, z=25) alloy powder.
[0042] Prepare diamond powder: Select diamond of model DSD80 with a particle size range of 170-200 mesh. Diamond powder is all bare diamond.
[0043] Mixing powder: Use three-dimensional powder mixer to mix Co x Ni y Ti z Zr 1-x-y-z The alloy powder and diamond powder were mixed for 24 hours. The diamond content was 12.5 vol.%, Co x Ni y Ti z Zr 1-x-y-z The alloy powder content is 87.5 vol.%.
[0044] 2. Preparation of CoNiTiZr-based diamond composite materials: The above Co x Ni y Ti z Zr 1-x-y-zAlloy powder-diamond mixed powder is filled into a graphite mold, and after pre-pressing, rapid hot pressing sintering is performed. Vacuum is drawn, and the temperature is raised from room temperature to 800°C at a rate of 85°C / min, and then kept warm for 2 minutes. At the same time, the pressure is raised to a forming pressure of 50MPa, and then the temperature is raised from 800°C to the sintering temperature of 1000°C at a rate of 100°C / min, and kept warm at the sintering temperature for 10 minutes.
[0045] Comparative Example 2 1. Material preparation: The material preparation of Comparative Example 2 is the same as that of Comparative Example 1.
[0046] 2. Preparation of high entropy alloy binder phase diamond composite materials: The above Co x Ni y Ti z Zr 1-x-y-z Alloy powder-diamond mixed powder is filled into a graphite mold, and after pre-pressing, rapid hot pressing sintering is performed. Vacuum is drawn, and the temperature is raised from room temperature to 800°C at a rate of 85°C / min, and then kept warm for 2 minutes. At the same time, the pressure is raised to a forming pressure of 50MPa, and then the temperature is raised from 800°C to the sintering temperature of 1000°C at a rate of 100°C / min, and kept warm at the sintering temperature for 20 minutes.
[0047] Example 1 1. Material preparation: The material preparation of Example 1 is consistent with that of Comparative Examples 1 and 2.
[0048] 2. Preparation of high entropy alloy diamond composites: The above Co x Ni y Ti z Zr 1-x-y-z Alloy powder-diamond mixed powder is filled into a graphite mold, and after pre-pressing, rapid hot pressing sintering is performed. Vacuum is drawn, and the temperature is raised from room temperature to 800°C at a rate of 85°C / min, and then kept warm for 2 minutes. At the same time, the pressure is raised to a forming pressure of 50MPa, and then the temperature is raised from 800°C to the sintering temperature of 1050°C at a rate of 125°C / min, and kept warm at the sintering temperature for 10 minutes.
[0049] Table 1 is a comparison of the wear amount of the materials after friction and wear tests between Example 1 and Comparative Examples 1 and 2
[0050] As shown in Table 1, in this embodiment 1, after being kept at 1050°C for 10 minutes under rapid hot pressing conditions and subjected to friction and wear test for 30 minutes, the wear amount of the composite material is less than that of the Si3N4 ball, which is 0.0013g, while the wear amount of the Si3N4 ball is twice that of the composite material, which is 0.0026g. The wear amounts of comparative examples 1 and 2 are both higher than that of the Si3N4 ball, which are 0.0049g and 0.0076g respectively. This indicates that the increase in sintering temperature helps promote the bonding of diamond and the binder phase matrix, further improving the bending strength and wear resistance of the composite material.
[0051] Table 2 is the test report of the wear ratio test of Example 1
[0052] As shown in Table 2, in this embodiment 1, the wear ratio is 843 after being kept at 1050°C for 10 minutes under the conditions of rapid hot pressing sintering according to JB / T 3235-2023. Compared with the composite materials made of other bonding phases, the wear ratio is relatively high, indicating that under this sintering condition, Co x Ni y Ti z Zr 1-x-y-z The composite material formed by the alloy binder phase and diamond has good wear resistance and bending strength.
Claims
1. A novel high entropy alloy binder phase diamond composite material, characterized in that: It consists of two parts: bonding phase alloy and diamond, of which the metal bonding phase content is 80-90vol.%, and the diamond content is 20-10vol.%; The element components and atomic percentages of the bonding phase alloy are: Co is 20-30%, Ni is 20-30%, Ti is 20-30%, and Zr is the balance; The diamond has a particle size of 170-200 meshes.
2. The novel high entropy alloy binder phase diamond composite material according to claim 1, characterized in that: In the bonding phase, in molar percentage, Co:Ni:Ti:Zr=1:1:1:
1.
3. The novel high entropy alloy binder phase diamond composite material according to claim 1, characterized in that: The diamond includes bare diamond particles having a complete crystal form.
4. The novel high entropy alloy binder phase diamond composite material according to claim 1, characterized in that: The model of the diamond is DSD80.
5. The novel high entropy alloy binder phase diamond composite material according to claim 1, characterized in that: The content of metal binder phase is 85~90%, and the content of diamond is 15-10vol.%.
6. The novel high entropy alloy binder phase diamond composite material according to claim 5, characterized in that: The metal binder phase content is 87.5% and the diamond content is 12.5 vol.%.
7. A method for preparing the novel high entropy alloy binder phase diamond composite material according to any one of claims 1 to 6, characterized in that: The required high entropy alloy binder phase powder and bare diamond powder are weighed and mixed according to the configuration ratio, and then pre-pressed and deformed and then hot-pressed and sintered to obtain the product; the hot-pressed sintering temperature is 1010-1100°C.
8. The method for preparing a novel high entropy alloy binder phase diamond composite material according to claim 7, characterized in that: The hot pressing sintering temperature is 1040-1060°C, the sintering time is about 10-20 minutes, and the sintering pressure is 30-50 MPa.
9. The method for preparing a novel high entropy alloy binder phase diamond composite material according to claim 7, characterized in that: First, evacuate to 5~50Pa, heat up from room temperature to 715~800℃ at a heating rate of 80~120℃ / min, keep warm for 1~3min, and pressurize to forming pressure of 30~50MPa; then heat up to sintering temperature of 950~1100℃ at a heating rate of 80~130℃ / min, and keep warm for 8~24min.
Citation Information
Patent Citations
Wear-resistant multi-principal-element alloy-diamond composite material as well as preparation method and application thereof
CN114134381A
Novel multi-principal element alloy-diamond grinding tool material as well as preparation method and application thereof
CN114645171A
High-entropy alloy-diamond superhard composite material with high self-sharpening and strong heat dissipation as well as preparation method and application of high-entropy alloy-diamond superhard composite material
CN114921677A
Efficient-grinding boron-containing high-entropy alloy and diamond combined superhard composite material and preparation method and application thereof
CN116574954A
Ultra-high strength multiphase high-entropy alloys
WO2023091169A1